2003
DOI: 10.1159/000068820
|View full text |Cite
|
Sign up to set email alerts
|

Combined Positron Emission Tomography and Magnetic Resonance Imaging for the Planning of Stereotactic Brain Biopsies in Children: Experience in 9 Cases

Abstract: Because brain tumors can be histologically heterogeneous, stereotactic brain biopsies (SBB) may lead to inaccurate diagnosis or grading. Positron emission tomography (PET) has been used in pediatric neuro-oncology to help in the understanding and management of brain neoplasms. We combined PET and magnetic resonance (MR) imaging in the planning of SBB in 9 children (5 males and 4 females, aged 2–14 years) with infiltrative, ill-defined brain lesions. Tracers used for PET were 18F-2-fluoro-2-deoxy-D-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 21 publications
(33 reference statements)
0
35
0
1
Order By: Relevance
“…Pirotte et al provided evidence that 11 C-MET PET improves the diagnostic yield of stereotactic brain biopsies and surgical management of brain tumors in children (6,30,31). Consistent with this finding, a first study using stereotactic biopsy guided by metabolic imaging with 18 F-FET PET enhanced the diagnostic yield in diffuse pediatric gliomas and disclosed unexpected hot spots (20).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Pirotte et al provided evidence that 11 C-MET PET improves the diagnostic yield of stereotactic brain biopsies and surgical management of brain tumors in children (6,30,31). Consistent with this finding, a first study using stereotactic biopsy guided by metabolic imaging with 18 F-FET PET enhanced the diagnostic yield in diffuse pediatric gliomas and disclosed unexpected hot spots (20).…”
Section: Discussionmentioning
confidence: 88%
“…In adult patients, PET using radiolabeled amino acids has been shown to improve diagnostic accuracy in patients with primary brain tumors, in particular gliomas (2,3). In pediatric brain tumor patients (4)(5)(6), several studies suggest that amino acid PET with the tracer methyl-11 C-L-methionine ( 11 C-MET) may improve the management. Results of these studies also implicate that 11 C-MET PET might be useful to differentiate neoplastic from nonneoplastic lesions in children and adolescents, in particular when a definite decision for further treatment based on a routine structural MR imaging procedures alone is difficult or impossible.…”
mentioning
confidence: 99%
“…Prior research demonstrates that 18 F-FDG and 11 C-MET improve the quality of therapeutic management of pediatric brain tumors at the diagnostic, surgical, and postoperative level, particularly in ill-defined infiltrative tumors. 18 F-FDG presents some limitations in defining targets for biopsy in low-grade pediatric tumors, whereas 11 C-MET appears also to be a better tracer than 18 F-FDG for delineating tumor boundaries and for residual tumor detection (25,26). Other studies found a correlation between 18 F-FDG uptake and tumor malignancy; however, there was significant overlap between different grades of malignancy (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…9 Ictal SPECT, in which tracer injection is performed during a seizure, also demonstrates focal hyperperfusion corresponding to the ictal onset zone with sensitivity similar to FDG-PET. 11,53 The SISCOM improves the sensitivity of SPECT by detecting regional differences between interictal and ictal perfusion. Preoperative SISCOM provides useful information for invasive electrode placement among children with multiple lesions, such as TSC.…”
Section: Preoperative Evaluationmentioning
confidence: 99%